MASALAH EKSISTENSI BANK TANAH DALAM SISTEM HUKUM PERTANAHAN NASIONAL DITINJAU DARI UUPA 1960 - Mbunai, La Ode; Bahari, Syaiful; Albab, S.H.S Ulil (Smart Education, 2025)
Abstract: Indonesia is one of country that is currently facing challenges in economic development. The main cause is the increasing of population, while that, the land supply is limited. The facts it was caused land conflict in various aspects and in some areas fighting over rare economics good, it is mean land. The government itself has difficulty obtaining land if it wants to build infrastructure or invite investment. Meanwhile, the available land regulations and land institutions are not sufficient to resolve the issue of land acquisition for economic development purposes. Therefore, Government Regulation Number 64 of 2021 concerning Land Bank Agency was issued. This study aims to analyze to the existence of the Land Bank when examined from the perspective of the UUPA. The method used in this study is doctrinal law with a statute approach. The conclusion of this study is that the existence of the Land Bank causes of conflict of legal norms in the national land law system and has not been able to create an effective solution in land acquisition for development public interest.Keyword: Land Scarcity, Land Acquisition, Land Bank, Conflict of Legal Norms, UUPAAbstrak: Indonesia termasuk negara yang kini menghadapi tantangan dalam pembangunan ekonomi. Penyebab utamanya adalah jumlah penduduk yang semakin meningkat namun persediaan tanah tidak bertambah. Akibatnya, di berbagai daerah seringkali terjadi konflik pertanahan karena memperebutkan barang ekonomi yang semakin langka dan berharga. Pemerintah sendiri mengalami kesulitan memperoleh tanah jika ingin membangun infrastruktur atau mengundang investasi. Sementara itu, regulasi dan lembaga pertanahan yang tersedia tidak cukup untuk menyelesaikan persoalan pengadaan tanah untuk kepentingan pembangunan ekonomi. Oleh kerena itu, diterbitkan Peraturan Pemerintah Nomor 64 Tahun 2021 tentang Badan Bank Tanah. Penelitian ini bertujuan untuk menganalisis eksistensi Bank Tanah jika dikaji dari perspektif UUPA. Metode yang digunakan dalam penelitian ini adalah hukum doktrinal dengan pendekatan perundang-undangan (statue approach). Kesimpulan dari penelitian ini adalah keberadaan Bank Tanah menimbulkan konflik norma hukum dalam sistem hukum pertanahan nasional dan belum dapat menciptakan solusi efektif dalam pengadaan tanah bagi pembangunan untuk kepentingan umum.Kata kunci: Kelangkaan Tanah, Pengadaan Tanah, Bank Tanah, Konflik Norma Hukum, UUPA